Liver graft pretreated in vivo or ex vivo by γ-aminobutyric acid receptor regulation - Hori, Tomohide (2012)
BACKGROUND: γ-Aminobutyric acid exists throughout the body, and the brain γ-aminobutyric acid receptor (GABAR) regulation reduces oxidative stress (OS). Effects of GABAR regulation in the liver are unknown. Ischemia or reperfusion injury after orthotopic liver transplantation (OLT) or shear stress after split OLT (SOLT) with a small-for-size graft causes OS-induced graft damage. Here, the strategic potential of graft pretreatment in vivo and ex vivo by GABAR regulation was investigated. MATERIALS AND METHODS: Recipient rats were divided into seven groups according to the graft pretreatments and graft types: (1) laparotomy, (2) OLT, (3) GABAR regulation in vivo and OLT, (4) GABAR regulation ex vivo and OLT, (5) SOLT, (6) GABAR regulation in vivo and SOLT, and (7) GABAR regulation ex vivo and SOLT. Survival study, biochemical assays, histopathologic or immunohistologic assessments, and Western blotting were performed at 6 h after OLT or SOLT. RESULTS: Graft pretreatment in vivo prolonged survival after SOLT. Histopathologic and biochemical profiles verified that graft pretreatment in vivo reduced graft damage after OLT or SOLT. Immunohistologically, graft pretreatment in vivo prevented apoptotic inductions after OLT or SOLT. The 4-hydroxynonenal confirmed the OS after OLT or SOLT, and graft pretreatment in vivo improved the OS. Graft pretreatment in vivo decreased ataxia-telangiectasia–mutated kinase and H2AX after OLT or SOLT. Graft pretreatment in vivo increased phosphatidylinositol 3 kinase and Akt after SOLT. In contrast, GABAR regulation ex vivo did not work. CONCLUSIONS: Graft pretreatment in vivo, not ex vivo, prevented the ischemia or reperfusion injury–mediated OS after OLT or SOLT via the ataxia-telangiectasia–mutated kinase/H2AX pathway and the shear stress–mediated OS after SOLT with small-for-size graft via the phosphatidylinositol 3 kinase/Akt pathway.